Penerapan Pelayanan Reservasi Paket Wisata oleh Customer Service PT Royal Asia Pasific Wholesaler di Era Pasca Pandemi Covid-19 - Maya Sofiana; Endang Supriyadi; Pajriatul Fachiroh (CV ODIS, 2023)
The purpose of this study is to find out the real picture of the events studied so that objective data can be easily obtained. Implementation of tour package reservation services by PT Royal Asia Pacific Wholesaler Customer Service in the post-Covid-19 Pandemic era. The research method used is a qualitative method. Data analysis techniques based on Miles and Huberman are data reduction (sorting, focusing and attention), data display and drawing conclusions. The implementation of tour package reservation services by Customer Service is carried out in several stages including the Greeting stage, starting stage, providing tour packages stage, tour package selection stage, tour package reservation/ordering stage, departure date determination stage, personal data filling stage, receiving report stage personal data, the stage of making receipts, the stage of receiving receipts, and the closing greeting stage